2007
DOI: 10.1080/13576500601112283
|View full text |Cite
|
Sign up to set email alerts
|

Visual laterality effects in readers of a deep and a shallow orthography

Abstract: Using a tachistoscopic split-field paradigm, hemifield asymmetry for single word recognition was examined in monolingual English speakers and in fluent bilingual English-Welsh speakers. A robust right hemifield advantage was found for both groups and both languages. Among bilinguals, the laterality index was significantly greater for Welsh than for English, supporting previous findings. The magnitude of the laterality index was unaffected by which language was learned first (Welsh or English) and by the age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…This finding is consistent with the literature, which generally showed that word processing in alphabetic languages with a shallow orthography (such as Italian) usually involves stronger LH lateralization than those with a deep orthography. For example, in their study, Beaton, Suller and Workman (2007) found a significantly larger RVF/LH advantage in naming Welsh words than English words in Welsh–English bilinguals (Welsh has a shallow orthography). As they found no effect of age and sequence of language acquisition on this difference in laterality, they argued that reading a language with a shallow orthography favors phonological decoding strategies, and this leads to stronger LH lateralization since phonological processing is typically LH lateralized.…”
Section: Discussionmentioning
confidence: 93%
“…This finding is consistent with the literature, which generally showed that word processing in alphabetic languages with a shallow orthography (such as Italian) usually involves stronger LH lateralization than those with a deep orthography. For example, in their study, Beaton, Suller and Workman (2007) found a significantly larger RVF/LH advantage in naming Welsh words than English words in Welsh–English bilinguals (Welsh has a shallow orthography). As they found no effect of age and sequence of language acquisition on this difference in laterality, they argued that reading a language with a shallow orthography favors phonological decoding strategies, and this leads to stronger LH lateralization since phonological processing is typically LH lateralized.…”
Section: Discussionmentioning
confidence: 93%
“…Since phonological processing is typically LH lateralized, consequently languages with a shallow orthography tend to have stronger LH lateralization in word processing than those with a deep orthography. For example, Beaton, Suller and Workman () found that Welsh‐English bilinguals had a significantly stronger RVF/LH advantage in naming Welsh words than naming English words (Welsh has a shallow orthography), and the lateralization effect was unaffected by which language was learned first or by age of second language acquisition (see also Workman, Brookman, Mayer, Rees & Bellin, ). In contrast to the argument that the difference between languages with a deep or shallow orthography is due to the use of LH‐lateralized phonological processing, our modeling results suggest that this difference may instead be due to the difference in spatial frequency content required for performing a consistent or inconsistent grapheme‐phoneme mapping (e.g., our alphabetic and logographic reading conditions in Simulation Two), since our model does not assume phonological processing being LH lateralized.…”
Section: Discussionmentioning
confidence: 99%
“…As the result, more HSF information is required as compared with the condition in which no systematic mapping exists between word form and pronunciation components (i.e., logographic mapping). Consistent with this finding, recent research has shown that readers of alphabetic languages that have a consistent grapheme‐phoneme correspondence (i.e., having a shallow orthography), such as Italian and Welsh, typically have a stronger LH lateralization in word processing as compared with readers of alphabetic languages that have a less consistent grapheme‐phoneme correspondence (i.e., deep orthography) such as English (e.g., Beaton, Suller, & Workman, ; Workman, Brookman, Mayer, Rees, & Bellin, ; see also Wimmer & Goswami, ). Lam and Hsiao () showed that bilinguals who learned a European language and English (both are alphabetic languages) had a stronger RVF/LH advantage in English word identification as compared with Chinese–English bilinguals (Chinese is a logographic whereas English is an alphabetic language).…”
Section: Discussionmentioning
confidence: 71%
“…Thus, our results here are consistent with this dual route approach to orthographic processing, demonstrating that both factors/routes can influence hemispheric lateralization of visual word processing. These two factors are able to explain hemispheric lateralization differences between the recognition of faces and words (e.g., Maurer & McCandliss, 2007;Rossion et al, 2003), between word recognition in different languages (e.g., Beaton et al, 2007;Maurer & McCandliss, 2007;Siok et al, 2009;Tan et al, 2005;Workman et al, 2000), between word recognition in monolinguals and bilinguals of different languages (e.g., Hsiao & Lam, 2013), and between the recognition of different character types in the Chinese orthography (e.g., Hsiao & Liu, 2010;Hsiao et al, 2007;Weekes & Zhang, 1999).…”
Section: Discussionmentioning
confidence: 99%